pharmaceutical-sciences 2019
DOI: 10.36468/pharmaceutical-sciences.511
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin-loaded Chitosan Nanoparticles: Preparation, Characterisation and Antibacterial Activity on Streptococcus pneumonia

Abstract: Chitosan (CS) is a linear copolymer of β-(1-4)linked 2-acetamido-2-deoxy-beta-D-glucopyranose and 2-amino-2-deoxy-3-D-glucopyranose, obtained by deacetylation of its parent polymer chitin, the second most abundant in nature after cellulose [1] . The bactericidal action of CS is well known and is due to an electrostatic interaction between NH 3 + groups of CS and phosphoryl groups of phospholipid components and lipopolysaccharides of bacterial cell membranes. This leads to an increase in the permeability format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
4
5
0
Order By: Relevance
“…Another interaction was observed when the volume ratio of tripolyphosphate (TPP) increased and the zeta potential decreased in. This confirmed that is largely attributed to the dependence of the formation of NPs on the TPP concentration that crosslinked with free NH2 groups [24]. Positive surface charges due to functional groups in CH chains are taken into account in prepared formulations.…”
Section: 1supporting
confidence: 64%
See 4 more Smart Citations
“…Another interaction was observed when the volume ratio of tripolyphosphate (TPP) increased and the zeta potential decreased in. This confirmed that is largely attributed to the dependence of the formation of NPs on the TPP concentration that crosslinked with free NH2 groups [24]. Positive surface charges due to functional groups in CH chains are taken into account in prepared formulations.…”
Section: 1supporting
confidence: 64%
“…The PDI value can vary from monodisperse systems to highly disperse systems with a values ranging from 0.00 to 1.00, respectively with a relatively larger size distribution indicating a PDI value greater than 0.5. However, for all formulations, especially for the CHNP formulation a small size distribution was observed [24,36,37]. In our results Positive overall of the values of Zeta Potential for CHNPs owing to the carboxyl group of chitosan (CH) [38].…”
Section: 1supporting
confidence: 51%
See 3 more Smart Citations